2011
DOI: 10.5125/jkaoms.2011.37.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Bone response around immediately placed titanium implant in the extraction socket of diabetic and insulin-treated rat maxilla

Abstract: Introduction: Dental implants are used routinely with high success rates in generally healthy individuals. By contrast, their use in patients with diabetes mellitus is controversial because altered bone healing around implants has been reported. This study examined the bone healing response around titanium implants placed immediately in rats with controlled and uncontrolled diabetes. Materials and Methods: Twenty rats were divided into the control, insulin-treated and diabetic groups. The rats received strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Similar to group A bone density showed significant increase (P ≤ 0.05) at three months postoperatively (1034.50 ±75.15HU) in comparison to two weeks interval (881.17±31.32HU) & significant decrease (P ≤ 0.05) of bone density measurements at six months postoperatively (781.83±46.84 HU) in comparison to the three months postoperative record. Table (6) When the three groups were compared to each other there was significant difference (P ≤0.…”
Section: Study Group B (Nano Bone)mentioning
confidence: 94%
See 1 more Smart Citation
“…Similar to group A bone density showed significant increase (P ≤ 0.05) at three months postoperatively (1034.50 ±75.15HU) in comparison to two weeks interval (881.17±31.32HU) & significant decrease (P ≤ 0.05) of bone density measurements at six months postoperatively (781.83±46.84 HU) in comparison to the three months postoperative record. Table (6) When the three groups were compared to each other there was significant difference (P ≤0.…”
Section: Study Group B (Nano Bone)mentioning
confidence: 94%
“…(3,4) with high survival rates reaching more than 95%. (3,(5)(6)(7) Authors described primary implant stability as a guiding factor for long term success predictability of immediate implants. (1,8) Clinical & experimental studies reported dimensional changes of the alveolar bone following tooth extraction with varying degrees of vertical & horizontal bone loss.…”
Section: Introductionmentioning
confidence: 99%